Engineered morphologies of β-NiS thin films via anionic exchange process and their supercapacitive performance. (5th May 2016) - Patil, A.M.; Lokhande, A.C.; Chodankar, N.R.; Kumbhar, V.S.; Lokhande, C.D.
Abstract: This effort dispenses an unprecedented electrochemical performance of highly porous nano-needles, stacked nano-needles, nano-plates and nano-flowers like morphological β -NiS thin films, synthesized through an anion exchange process using hydrothermally prepared Ni(OH)2 thin films. The stacked nano-needle structured β -NiS thin film shows maximum specific capacitance (Cs ) of 415.78 Fg − 1 at current density of 0.5 mA cm − 2 in 2 M KOH electrolyte with electrochemical stability up to 91% after 2000 cyclic voltammetry (CV) cycles. In addition, symmetric flexible solid state supercapacitor (FSS-SCs) device fabricated using β -NiS thin films and polyvinyl alcohol-lithium perchlorate (PVA–LiClO4 ) as a polymer gel electrolyte, shows acceptable Cs of 55.83 Fg − 1 at scan rate of 10 mV s − 1 within operating potential window of 1.2 V. The symmetric FSS-SCs device manifests maximum specific energy density of 9.30 Wh kg − 1 and specific power density of 666 W kg − 1 along with better electrochemical stability of 90% after 1500 CV cycles. More interestingly, symmetric FSS-SCs device easily light up the panel of 40 red light emitting diodes (LEDs) texted as 'CDL' for 45 s after charging for 30 s. Graphical abstract: The schematic of NiS formation on SS substrate with different steps of anion exchange process. The inset shows actual demonstration of fabricated symmetric flexible solid state supercapacitor (FSS-SC) device by glowing the 40 LED's texted as 'CDL'. Highlights: The different nanostructures of β -NiS thin films developed using simple chemical anion exchange process. The stacked nano-needles based β -NiS thin film (NiS2) exhibit excellent electrochemical features. The β -NiS thin film based symmetric FSS-SCs device glows 40 red LEDs for 45 s, after charging for 30 s.